STUDENTS’ PERCEPTION OF CAREER IN HOSPITALITY INDUSTRY (International Journal of Food and Nutritional Sciences, 2022)
This paper is an attempt to find out the factors which the students consider as important while choosing a career in hospitality industry. The data has been analyzed to evaluate the relationship between students’ perception and their intention to initiate their career in hospitality industry. To achieve the research objectives primary data was collected from a sample of 140 hospitality students of selected hospitality institutions of Punjab region of India. Students believe work well with colleagues, finding job respectable, hygienic work environment, a sense of surety to find job and guaranteed career growth, and perceive job security as a highest rated factors. The results of the relationship between the students perception of careers in the industry and their intention to follow a career path in the industry indicated a positive association between the two variables (r=.72, p=.000) and also indicated favorable perceptions correlated with the intention.